ナンキョク マクマードサウンド シュウヘン ノ ジシン カツドウ - 神沼, 克伊; カミヌマ, カツタダ; KAMINUMA, Katsutada (国立極地研究所, 1976)
P(論文) 日本,アメリカ,ニュージーランド3国共同事業として,ドライバレー掘削プロジェクト(DVDP)が1971-1976年の夏のシーズン,アメリカのマクマード基地を中心に行われた.このプロジェクトの一環として, 1974-75, 75-76年のシーズンに微小地震の観測を行った.観測は,マクマード基地北東城のアライバル・ハイツで3週間,オブザベーション・ヒル北方麓で1ヵ月,ドライバレーのティラー谷で10日,バンダ基地で3週間,実施した.マクマード基地は火山島であるロス島の南西端に位置し,活火山エレブスの火口から30km離れている.マクマード基地付近での観測からは,1日に1個程度の頻度で微小地震が発生していることが明らかになった.また大陸にあるドライバレーでの観測では,2日に1個程度の発生頻度であった.この二つの事実からマクマードサウンド周辺の地震活動は,2日に1個程度の割合で微小地震が発生し,火山地域ではそれに重なりさらに同程度の割合で微小地震が起こるものと推定される. For the purpose of observing micro earthquakes around the McMurdo Sound area and volcanic earthquakes around Mt. Erebus on Ross Island, in Antarctica, seismological observations were carried out in the austral summer seasons of 1974-75 and 1975-76, as one of the research programs of the Dry Valley Drilling Project (DVDP) which was carried out by scientists from Japan, New Zealand and the United States. The sites and duration of observations are as follows: 1) Arrival Heights, McMurdo Station (three weeks in 1974-75); 2) Lake Leon, Taylor Valley, one of the dry valleys in Victoria Land (10 days in 1974-75); 3) Northern foot of Observation Hill, McMurdo Station (one month in 1975-76). The micro seismic activity around McMurdo Station obtained from the observations is about one earthquake per day, and that in the Taylor Valley is about 0.5. Background seismicity around the McMurdo Sound area is estimated to be one micro earthquake every two days. In addition to this background seismicity, one earthquake occurs in every two days in the volcanic area around McMurdo Station. departmental bulletin paper